World best metro practice Meilleur metro mondiale : proceedings of the international conference, 10-11 April 2002. (Thomas Telford, 2010)
Under the auspices of the Transport Board, the ICE mounted a two-day conference to consider metros, the best practice on a worldwide basis. It focused on systems that are, or will be, benchmarks both of excellence and best practice. The proceedings are provided here.